2016
DOI: 10.1631/jzus.b1500219
|View full text |Cite
|
Sign up to set email alerts
|

Function, kinetic properties, crystallization, and regulation of microbial malate dehydrogenase

Abstract: Abstract:Malate dehydrogenase (MDH) is an enzyme widely distributed among living organisms and is a key protein in the central oxidative pathway. It catalyzes the interconversion between malate and oxaloacetate using NAD + or NADP + as a cofactor. Surprisingly, this enzyme has been extensively studied in eukaryotes but there are few reports about this enzyme in prokaryotes. It is necessary to review the relevant information to gain a better understanding of the function of this enzyme. Our review of the data g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 89 publications
3
32
0
1
Order By: Relevance
“…The affinity of oxaloacetate and NADH for Sy MDH was higher than the affinity of malate and NAD + , respectively ( Table 1 ). Generally, bacterial MDHs show higher affinity for oxaloacetate than malate ( Takahashi-Íñiguez et al, 2016 ), and Sy MDH was consistent with this. When comparing the substrate affinity among bacterial MDHs, the K m (malate)/ K m (oxaloacetate) ratio in descending order is as follows: N. europaea (250) , Synechocystis 6803 (210), Syntrophic propionate-oxidising bacterium strain MPOB (80.0), and Methanobacterium thermoautotrophicum (13.3) ( Table 2 ).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The affinity of oxaloacetate and NADH for Sy MDH was higher than the affinity of malate and NAD + , respectively ( Table 1 ). Generally, bacterial MDHs show higher affinity for oxaloacetate than malate ( Takahashi-Íñiguez et al, 2016 ), and Sy MDH was consistent with this. When comparing the substrate affinity among bacterial MDHs, the K m (malate)/ K m (oxaloacetate) ratio in descending order is as follows: N. europaea (250) , Synechocystis 6803 (210), Syntrophic propionate-oxidising bacterium strain MPOB (80.0), and Methanobacterium thermoautotrophicum (13.3) ( Table 2 ).…”
Section: Discussionsupporting
confidence: 63%
“…The reductive reaction catalysed by bacterial MDHs is inhibited by TCA cycle metabolites, such as excess oxaloacetate and divalent metal ions ( Takahashi-Íñiguez et al, 2016 ). Therefore, we measured the activity of Sy MDH in the reductive reaction in the presence of various effectors.…”
Section: Resultsmentioning
confidence: 99%
“…Whether the detailed mechanism is consistent with E. coli requires further study. In addition, this protein can catalyze the interconversion between malate and oxaloacetate with the help of cofactor NAD + or NADP + and plays a critical role in the central oxidative pathway of living organisms [33]. In gram-negative bacteria, this protein generally forms a dimeric molecule and participates in the tricarboxylic acid (TCA) cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetic parameters for MexMDH-His 8 were calculated using the decrease in absorbance caused by the enzymatic oxidation of NADH to NAD + (" = 6.22 mM À1 cm À1 ) in the presence of oxaloacetate. We obtained a Michaelis constant (K m ) of 36.8 AE 0.6 mM for oxaloacetate, which compares favorably to a serine-type methanotroph (Rozova et al, 2015) and is twofold to tenfold lower then those observed for MDHs found in many aerobic bacteria (Rozova et al, 2015;Takahashi-Íñ iguez et al, 2016). MexMDH catalyzes the reduction of oxaloacetic acid with a k cat of (4.6 AE 0.1) Â 10 2 s À1 , yielding a catalytic efficiency k cat / K m of (1.3 AE 0.3) Â 10 7 M À1 s À1 .…”
Section: Molecular-weight Determination and Kineticsmentioning
confidence: 58%